No Emergence of Colistin Resistance in the Respiratory Tract of Lung Transplant Patients Treated With Inhaled Colistin - Nathalie Grall; Nathalie Grall; Maksud Assadi; Marina Esposito-Farese; Brice Lortat-Jacob; Sébastien Tanaka; Sébastien Tanaka; Enora Atchade; Jonathan Messika; Jonathan Messika; Jonathan Messika; Vincent Bunel; et al. (Transplant International)
Secondary prophylaxis using inhaled colistin (IC) was implemented to prevent recurrences of Pseudomonas aeruginosa or extended-spectrum β-lactamase-producing Enterobacterales (ESBL-PE) pneumonia during the postoperative intensive care unit (ICU) stay after lung transplantation (LT). We evaluated the risk of emergence of colistin resistance in the respiratory tract during secondary IC prophylaxis. We conducted a prospective, single-centre, observational study of all adult patients who underwent LT between 1 July 2018 and 30 June 2019. IC was started and continued for at least 90 days for P. aeruginosa or ESBL-PE pneumonia. During the 90 days following LT, all respiratory samples were routinely tested for the presence of GNB of reduced susceptibility to colistin. Twenty-seven (38.6%) of the 70 included patients received IC. Among the 867 respiratory samples tested, IC did not promote the emergence of bacterial species with natural or acquired resistance to colistin (incidence-rate ratio of 0.21 [0.03–1.58], p = 0.13 and 1.68 [0.55–5.12], p = 0.37, respectively). Our study suggests no association between the use of IC and an increased risk of colistin resistance in the respiratory tract within 90 days of LT.